Effects of additional amount of carbon micro-coils on the dielectric properties of its composite sheet (Journal of Bangladesh Academy of Sciences, 2014)
The morphology and dielectric properties of carbon micro-coils (CMC) composite sheet wereexamined. Frequency dependence of dielectric parameters; dielectric loss angle (?), dielectric losstangent (tan?) and relative dielectric constant ( ?r) were measured on single and double-helixcomposite sheet. It was found that these parameters of CMC/polysilicone composites extensivelychanged with the additional amount of CMC with polysilicone resine. It was also observed that thehigher additional amount (wt%) of CMC is appropriate for high response. DOI: http://dx.doi.org/10.3329/jbas.v38i1.20210 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 1, 39-47, 2014